An Experimental Assessment into the Pressure and Thermal Efficacy of Chemically Synthesized Nanofluids in Computer Cooling Applications. (11th November 2022) - Anish, M.; Bency, P.; Jayaprakash, V.; Jayaprabakar, J.; Joy, Nivin; Sahaya Susmi, S. K.; Arunkumar, T.
Abstract : In order to maintain ideal working conditions by reducing heat from the system, a certain mechanism must be put into place. This research aims to investigate the effects of nanofluids on the performance of microchannel heating components used in computer cooling methods. The mixture of 25% ethylene glycol and 75% alkaline water is used to create the working fluids in the experiment. The combination contains nanoparticles of SiC, TiO2, and ZnO. It is between 25 and 40°C, includes 0.25%–1.5% nanoparticles, and has a volume flow rate of 0.025–0.080 kg/s. The temperature of the central processing unit, the rate of heat transfer, pressure losses, and pumping power have all been researched in relation to the thermal properties of nanofluids and base fluids. Data show that SiC–EG/AW at 1.5% concentration and 0.080 kg/s has a 31% higher coefficient of heat transfer than the base fluid and a temperature that is 9% lower than that of the other nanofluids. This is due to the fact that SiC–EG/AW has the highest pumping force power and TiO2 –EG/AW has the lowest pressure decrease. Because the nanofluid performs better than the basic fluid at cooling computers, a little boost in pumping force and pressure reduction may be acceptable.